Perception of peer teaching on learning anatomy: a qualitative study - Faiza Umbreen; Khadija Qamar; Tayyaba Faisal; Rafia Asjid; Saleem Ahmad Khan; Sumyyia Bashir; Amna Tasawar (Journal of the Pakistan Medical Association, 2020)
Abstract The aim of this study was to identify the effectiveness of peer-assisted learning while giving presentation on assigned anatomy topics in class by medical students for enhancement of their learning and communication skills. Sixty top performing students were selected for the study. They were given assigned topics related to anatomy to presented in the class after taking their consent. The duration of the study was 32 weeks. At the completion of the projects by the students, each of them was interviewed for three to five minutes; the questions were very precise and few in number and were then analysed. Focal group discussions were conducted from the rest of the class who were the audience and enjoyed the activity. The study showed that by conducting such an activity among medical students their knowledge about the subject, communication and teaching skills and confidence are enhanced.